‟JULES ET JIM”, DE FRANÇOIS TRUFFAUT OU L’INSOUTENABLE LÉGÈRETÉ DU FÉMININ - Mihaela ȚURCANU LAZAROV (Studia Universitatis Babeș-Bolyai. Philosophia)
Jules et Jim by François Truffaut or the Unbearable Lightness of the Feminine. Truffaut’s movie Jules et Jim (« Jules and Jim ») is an intimist movie but also a fresco of Europe throughout the first half of the 20th century, as it was torn apart by the two world wars and Nazism. At the same time, the film tells the story of the friendship that began during the Belle Epoque between two intellectuals, a French (Jim) and a German (Jules), both madly in love with an English teacher (Catherine). In the insular tradition of the Elizabethan theatre, this is a story about love, treason, jealousy, hate, and finally murder and suicide. In its structure, it is a mix of farce, sentimental drama turned into tragedy, and which in the end reveals itself as a comedy of errors, with, nevertheless, very serious themes: love and war, desire and drives, femininity, maternity and semblance, competition between men for a woman etc. This movie brilliantly represents the Nouvelle vague and is a proof that Freud and Lacan were right when they established once and for all that the unconscious is a fundamental and necessary scene. Human destiny is set and its mysterious scripts are played out - from sexuality to death, from Eros to Thanatos - as the subject’s fantasy, the window through which he or she tackles reality.